2004
DOI: 10.1021/ja0390146
|View full text |Cite
|
Sign up to set email alerts
|

A Zeolitic Organo−Metallophosphate Hybrid Material with Bimodal Porosity

Abstract: The first metal carboxylatophosphate, NTHU-2, contains inorganic ZnHPO4 layers linked by BDC units (BDC = 1,4-benzene dicarboxylate or terephthalic anion); the three-dimensional anionic framework has large pores with the smallest diameter being 1.36 nm; N2 sorption isotherms reveal both micro- and mesoporosity; the new material is photoluminescent and disassembles in water wherein the discharged organic fragments form mixed crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…The residue, confirmed to contain only the inorganic material from NTHU-10, also gave a weak blue emission line at 470 nm ( Figure S2a in the Supporting Information), a blue shift by 15 nm as compared with that of 10 d. The result indicated that the emission peak observed at 485 nm for NTHU-10 should originate from the inorganic [Zn 2 -(H 2 PO 4 ) 2 ] 2+ unit. Next, the emission peak at 515 nm was [15] 1D chains in NTHU-8, [14] and 0D clusters in NTHU- 10. considered to be attributed to ligand-to-metal charge transfer LMCT from O btec À Zn bonds which, as in MOF structures, are often observed in the region from 500 to 530 nm. [4,20] Meanwhile, we prepared a solid sample of K 4 (btec) [21] to measure the ligand-based emission of btec 4À .…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The residue, confirmed to contain only the inorganic material from NTHU-10, also gave a weak blue emission line at 470 nm ( Figure S2a in the Supporting Information), a blue shift by 15 nm as compared with that of 10 d. The result indicated that the emission peak observed at 485 nm for NTHU-10 should originate from the inorganic [Zn 2 -(H 2 PO 4 ) 2 ] 2+ unit. Next, the emission peak at 515 nm was [15] 1D chains in NTHU-8, [14] and 0D clusters in NTHU- 10. considered to be attributed to ligand-to-metal charge transfer LMCT from O btec À Zn bonds which, as in MOF structures, are often observed in the region from 500 to 530 nm. [4,20] Meanwhile, we prepared a solid sample of K 4 (btec) [21] to measure the ligand-based emission of btec 4À .…”
mentioning
confidence: 94%
“…Discovery of NTHU-10 marks completion of a hybrid framework system that contains all three possible dimensionalities of inorganic tectons ( Figure 3). [14,15] The four optical analogues 10 a, 10 b, 10 c and 10 d were found to share the common structure of NTHU-10. [16] The unique structure contains discrete 4-ring clusters of [Zn 2 -(H 2 PO 4 ) 2 ] 2+ as the 0D inorganic substructure, which are interlinked by four-connected btec 4À ligands into a hybrid [Zn 2 (H 2 PO 4 ) 2 (btec)] 2À layer.…”
mentioning
confidence: 99%
“…Recently, the oxalate unit cross-link the inorganic parts and act as a bridge in the phosphate-oxalates giving rise to a new family of inorganic/organic hybrid materials [14][15][16]. Large numbers of template-directed metal phosphate-oxalates have recently been prepared and characterized [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Wang and co-workers successfully synthesized two organic template-directed indium phosphite compounds |C 2 N 2 H 10 |[In(OH) 3 (HPO 3 )] [10] and |C 4 N 2 H 12 |[In 2 -(HPO 3 ) 3 (H 2 PO 3 ) 2 ] [11]. Subsequently, two indium phosphite compounds were reported by Liu et al [12,13].Recently, the oxalate unit cross-link the inorganic parts and act as a bridge in the phosphate-oxalates giving rise to a new family of inorganic/organic hybrid materials [14][15][16]. Large numbers of template-directed metal phosphate-oxalates have recently been prepared and characterized [17][18][19][20].…”
mentioning
confidence: 99%
“…[9][10] While major attention has been focused on pore-size-related absorption properties, we have concurrently discovered extraordinary photoluminescence (PL) properties in openframework metal phosphates. [11][12][13][14][15][16] We discovered two metal phosphates, NTHU-4 [12] and NTHU-6, [13] which have novel nanoporous structures. These metal phosphates, unlike commercialized or developed color-conversion phosphors with emissions that originate from emitting activators doped into condensed host lattices, [17] contained no metal activators or any form of chromophores, but could emit intense yellow light under the excitation of near-ultraviolet (NUV) and blue light.…”
mentioning
confidence: 99%